Peningkatan Aktivitas dan Motivasi Belajar Siswa Kelas VII melalui Model Pembelajaran Project Based Learning di MTsN 1 Blitar - Rizqa Nadhifah; Hendra Pratama (Universitas 45 Surabaya, 2024)
The background of this research is the lack of student activity in social studies learning, such as students being less active in asking questions related to the material, students less active in giving responses or answers given by the teacher, students never writing or taking notes on lesson material, no discussion activities, lack of interest in working on or solving the problems given. Apart from that, student motivation in learning social studies is still low, namely students are less enthusiastic about learning social studies and less diligent in facing the tasks given by the teacher. Some of these problems resulted in the average daily test score for students in the observation class being less than the maximum, namely 76, this shows that there were 23 students whose scores were still below the KKM score for social studies subjects, namely 80, while students who finished with scores above the KKM were only a total of 13 students from the total number of 36 students. The formulation of the problem in writing this thesis includes: (1) Is there an influence on the application of the Project Based Learning learning model on the learning activities of Class VII social studies students at MTs Negeri 1 Blitar?, (2) Is there an influence on the application of the Project Based learning model Learning on the learning motivation of students in Class VII social studies at MTs Negeri 1 Blitar?. Meanwhile, the aim of this research is to find out: (1) whether there is an effect of implementing the Project Based Learning learning model on student learning activities in class VII social studies at MTs Negeri 1 Blitar. (2) Is there an effect of implementing the Project Based Learning learning model on student learning motivation in class VII social studies at MTs Negeri 1 Blitar. The benefit of this research for students is that it is hoped that it can increase student learning activity and motivation. For teachers, the Project Based Learning learning model can be used as an approach to learning that can be applied in thematic learning. For schools, as consideration for school principals to improve the quality of education at MTs Negeri 1 Blitar and can be used as input in order to improve the quality of education in class VII thematic learning. And for researchers, it is useful as an effort to develop the application of the Project Based Learning Model directly because researchers can find out and understand problems in schools, as well as to fulfill one of the requirements for completing undergraduate studies in writing scientific papers at UIN Sayyid Ali Rahmatullah Tulungagung, Faculty of Tarbiyah and Teacher Training, Tadris Social Sciences Study Program. The research method used in this research is quantitative research with a Quasi Experimental Research approach. The research was carried out by dividing students into two groups, namely the control group which took part in conventional learning and the experimental group which applied the Project Based Learning learning model. The population in this study was all students in class VII MTsN 1 Blitar, while the sample used was class VII-7 and VII-11, totaling 72 students. This is used to explore or obtain research data that will be used by researchers. The research results show that the application of the Project Based Learning learning model has a positive effect on students' learning activities and learning motivation. Students who take part in learning with this model show a significant increase in learning activity and learning motivation compared to students who take part in conventional learning. This is proven through the results of questionnaire data analysis and observation sheets as well as hypothesis testing carried out using the Independent Sample Test. The significance value obtained from the results of the learning activity questionnaire hypothesis test is (2-tailed) 0.000 < 0.05 and the significance value from the learning activity observation sheet is (2-tailed) 0.000 < 0.05. Meanwhile, the significance value of the hypothesis test results of the learning motivation questionnaire is (2-tailed) 0.003 < 0.05 and the significance value of the learning motivation observation sheet is (2-tailed) 0.001 < 0.05. This indicates that H0 is rejected and Ha is accepted, indicating that there is a significant influence from the application of the Project Based Learning learning model on students' learning activities and learning motivation..